Automatic inference and measurement of 3D carpal bone kinematics from single view fluoroscopic sequences - Chen, Xin; Graham, Jim; Hutchinson, Charles; Muir, Lindsay (Institute of Electrical and Electronics Engineers, 2012)
We present a novel framework for estimating the 3D poses and shapes of the carpal bones from single view fluoroscopic sequences. A hybrid statistical model representing both the pose and shape variation of the carpal bones is built, based on a number of 3D CT data sets obtained from different subjects at different poses. Given a fluoroscopic sequence, the wrist pose, carpal bone pose and bone shapes are estimated iteratively by matching the statistical model with the 2D images. A specially designed cost function enables smoothed parameter estimation across frames and constrains local bone pose with a penalty term. We have evaluated the proposed method on both simulated data and real fluoroscopic sequences and demonstrated that the relative poses of carpal bones can be accurately estimated. One condition that may be assessed using this measurement is dissociation, where the distance between the bones is larger than normal. Scaphoid–Lunate dissociation is one of the most common of these. The error of the measured 3D Scaphoid–Lunate distances were 0.75+/-0.5 mm for simulated data (25 subjects) and 0.93+/-0.47 mm for real data (15 subjects). We also propose a method for constructing a “standard” pathology measurement tool for automatically detecting Scaphoid–Lunate dissociation conditions, based on single-view fluoroscopic sequences. For the simulated data, it produced 100% sensitivity and specificity. For the real data, it achieved 83% sensitivity and 78% specificity.